2008
DOI: 10.1152/ajprenal.00019.2007
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of anti-Thy1-glomerulonephritis by PPAR-γ agonism without increase of endothelial progenitor cell homing

Abstract: Westerweel PE, den Ouden K, Nguyen TQ, Goldschmeding R, Joles JA, Verhaar MC. Amelioration of anti-Thy1-glomerulonephritis by PPAR-␥ agonism without increase of endothelial progenitor cell homing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…41,42 Moreover, PPAR-g agonists can directly decrease glomerular TGF-b expression in both diabetic and nondiabetic model rats independent of its effect on glycemic control. 19,43 In vitro studies by Hong et al demonstrated that cytoplasmic phosphorylation of Smad2/3 that act to stimulate TGF-b-dependent nuclear events was unaffected by PPAR-g agonists, whereas PPAR-g agonists were found to inhibit Smad2/3 phosphorylation either through direct interaction with TGFbR-I or with nonphosphorylated Smads. 44 In this study, we demonstrated that a PPAR-g agonist significantly reduced the expression of both TGF-b1 and TGFbR-I at 7 days after UUO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 Moreover, PPAR-g agonists can directly decrease glomerular TGF-b expression in both diabetic and nondiabetic model rats independent of its effect on glycemic control. 19,43 In vitro studies by Hong et al demonstrated that cytoplasmic phosphorylation of Smad2/3 that act to stimulate TGF-b-dependent nuclear events was unaffected by PPAR-g agonists, whereas PPAR-g agonists were found to inhibit Smad2/3 phosphorylation either through direct interaction with TGFbR-I or with nonphosphorylated Smads. 44 In this study, we demonstrated that a PPAR-g agonist significantly reduced the expression of both TGF-b1 and TGFbR-I at 7 days after UUO.…”
Section: Discussionmentioning
confidence: 99%
“…For example, activation of PPAR-g reduced glomerulosclerosis and apoptosis in various models including the 5/6 nephrectomy model, passive Heymann nephritis model, crescentic glomerulonephritis model, acute mesangial proliferative glomerulonephritis model, and renal ischemia-reperfusion injury model. [16][17][18][19][20][21] In vitro studies have focused on the effect on mesangial cells, where PPAR-g activation exerts antiproliferative and antifibrotic effects 22,23 via the modulation of transforming growth factor-b1 (TGF-b1)-mediated pathways. 24 TZDs also reduced the secretion of macrophage chemotactic protein-1 (MCP-1), a proinflammatory chemokine, in human HK-2 cells exposed to high concentrations of glucose.…”
mentioning
confidence: 99%
“…PGZ also stimulates the expression of TGF β and TGF β receptor [49], and thus initiates EPC conversion to the VSMC phenotype [50]: increased VSMC presence may stabilize the neovasculature and thus reduce angiogenesis. This may explain why PPAR γ agonists ameliorate glomerulonephritis in mouse model without increase in EPC homing [51]. …”
Section: Anti-angiogenic Effects Of Pparγ In Diverse Cell Types: Ementioning
confidence: 99%
“…They have recently been attracting considerable attention as renoprotective drugs useful for treating renal diseases that are associated with metabolic disorders and diabetic nephropathy 7,10–12 . There have also been a few reports indicating that PPAR‐γ agonists have renoprotective effects in cases of non‐metabolic renal disease, 13–15 and we recently demonstrated that Pio significantly reduced proteinuria and interstitial fibrosis in the SHC rat 7 . The experimental models analyzed in those few reports are associated with massive proteinuria, and the proteinuria was prominently decreased by treatment with a PPAR‐γ agonist.…”
Section: Discussionmentioning
confidence: 86%